APOL1 risk allele RNA contributes to renal toxicity by activating protein kinase R. (December 2018) - Okamoto, Koji; Rausch, Jason; Wakashin, Hidefumi; Fu, Yulong; Chung, Joon-Yong; Dummer, Patrick; Shin, Myung; Chandra, Preeti; Suzuki, Kosuke; Shrivastav, Shashi; Rosenberg, Avi; Hewitt, Stephen; et al.
Abstract APOL1 risk alleles associate with chronic kidney disease in African Americans, but the mechanisms remain to be fully understood. We show thatAPOL1 risk alleles activate protein kinase R (PKR) in cultured cells and transgenic mice. This effect is preserved when a premature stop codon is introduced toAPOL1 risk alleles, suggesting thatAPOL1 RNA but not protein is required for the effect. Podocyte expression ofAPOL1 risk allele RNA, but not protein, in transgenic mice induces glomerular injury and proteinuria. Structural analysis of the APOL1 RNA shows that the risk variants possess secondary structure serving as a scaffold for tandem PKR binding and activation. These findings provide a mechanism by which APOL1 variants damage podocytes and suggest novel therapeutic strategies. Okamoto et al. report that APOL1 RNA, but not protein, expressed from chronic kidney disease (CKD)-associated alleles activates protein kinase R, inducing glomerular injury in a mouse model. The secondary structure of APOL1 risk variant RNA acts as a scaffold for protein kinase R, suggesting potential therapeutic strategies for CKD.